2017
DOI: 10.1002/ceat.201700182
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of CO2 Absorption Using Nanofluids in a Hollow‐Fiber Membrane Contactor

Abstract: To remove CO 2 from N 2 /CO 2 gas mixtures, a-Al 2 O 3 /water and g-Al 2 O 3 /water nanofluids have been used in a dialysis nanoporous hollow-fiber membrane contactor. The mass transfer coefficient, CO 2 removal efficiency, and CO 2 concentration profile were determined under different operating conditions. The results showed that the addition of a-Al 2 O 3 and g-Al 2 O 3 nanoparticles to the solvent increased the mass transfer rate, and by raising the nanofluid concentration, the removal efficiency enhanced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Ansaripour et al also confirmed this finding by using α-Al 2 O 3 /water and γ-Al 2 O 3 /water nanofluids with a nano-porous hollow fiber dialysis membrane contactor to remove CO 2 from N 2 /CO 2 gas mixtures. The results showed that the increases in the removal efficiency of α-Al 2 O 3 /water and γ-Al 2 O 3 /water nanofluids with a concentration of 0.02 vol% in comparison with distilled water were 12.2% and 21.6%, respectively [85]. Olle et al used functional magnetic nanoparticles to enhance oxygen mass transfer and found that it was increased up to six-fold by a water-based Fe 3 O 4 nanofluid [86].…”
Section: Nanofluidsmentioning
confidence: 99%
“…Ansaripour et al also confirmed this finding by using α-Al 2 O 3 /water and γ-Al 2 O 3 /water nanofluids with a nano-porous hollow fiber dialysis membrane contactor to remove CO 2 from N 2 /CO 2 gas mixtures. The results showed that the increases in the removal efficiency of α-Al 2 O 3 /water and γ-Al 2 O 3 /water nanofluids with a concentration of 0.02 vol% in comparison with distilled water were 12.2% and 21.6%, respectively [85]. Olle et al used functional magnetic nanoparticles to enhance oxygen mass transfer and found that it was increased up to six-fold by a water-based Fe 3 O 4 nanofluid [86].…”
Section: Nanofluidsmentioning
confidence: 99%
“…144 The improvement of gas solubility into the absorbent by the addition of a third dispersed phase, i.e., nanoparticles, was investigated by several researchers. [145][146][147] However, a few studies have been conducted on CO2 desorption: J.W. Lee et al 148 and Lee et al 149 compared the CO2 regeneration efficiency of nanofluids (Al2O3 and SiO2 nanoparticles dispersed in DI water and methanol) and pure solvents.…”
Section: Nanofluidsmentioning
confidence: 99%
“…7) Especially, microstructural features such as dislocation density, grain size, and the presence of solute atoms and precipitates affect the motion of magnetic domain walls, which, in turn, affects the characteristic magnetic parameters such as coercivity, remanence, hysteresis loss, and saturation magnetization 7,8) Renzetti et al revealed that a decrease in coercivity was resulted from the grain size increment in ferritic-martensitic steel. 9) Similarly, a theoretical work performed by Sablik et al showed that there was a linear relationship between coercivity and the inverse of the grain size.…”
Section: Effect Of Microstructural Features On Mechanical and Magnetimentioning
confidence: 99%